New Phlebotomine Sandflies of the walkeri group (Diptera: Psychodidae) from Pará State, Brazil, with a pictorial key 1 - Lee Ryan; Habib Fraiha; Ralph Lainson; Jeffrey J. Shaw (Memorias do Instituto Oswaldo Cruz, 1986)
The male and female of Lutzomyia carmelinoi n.sp., and the female only of L. baculus and L. williamsi, (Diptera:Psychodidae) are described and illustrated from specimens collected in Pará state, Brazil. A pictorial key is presented to these and the other members of the walkeri group. Lutzomyia carmelinoi n.sp., uma nova espécie e as fêmeas de L. baculus e L. williamsi são descritas com uma chave para os outros flebótomos do grupo walkeri.